Neuromodulating roles of estrogen and phytoestrogens in cognitive therapeutics through epigenetic modifications during aging - Singh, Padmanabh; Paramanik, Vijay (Frontiers in Aging Neuroscience, 2022)
Estrogen (E2) plays important role in regulating hippocampal learning and memory. The decline of E2 after menopause affects learning and memory and increases the risk of neurodegenerative diseases like Alzheimer’s disease (AD). Additionally, from the estrogen receptor (ER) mediated gene regulation; E2 also regulates gene expression at the transcriptional and posttranscriptional levels through epigenetic modifications. E2 recruits a number of proteins called co-regulators at the promoter region of genes. These co-regulators act as chromatin modifiers, alter DNA and histone modifications and regulate gene expression. Several studies show that E2 regulates learning and memory by altering chromatin at the promoters of memory-linked genes. Due to structural similarities with E2 and low side effects, phytoestrogens are now used as neuroprotective agents to recover learning and memory in animal models as well as human subjects during aging and different neurological disorders. Growing evidences suggest that apart from anti-oxidative and anti-inflammatory properties, phytoestrogens also act as epigenetic modifiers and regulate gene expression through epigenetic modifications. The epigenetic modifying properties of phytoestrogens are mostly studied in cancers but very little is known regarding the regulation of synaptic plasticity genes, learning and memory and neurological disorders. In the present article, we discussed the epigenetic modifying properties of E2 and the roles of phytoestrogens as epigenetic modifiers in the brain to recover and maintain cognitive functions.